2005
DOI: 10.1212/01.wnl.0000187070.35365.d7
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of high-dose (3,000 mg/day) coenzyme Q10 in ALS

Abstract: An open-label dose-escalation trial was performed to assess the safety and tolerability of high doses of coenzyme Q10 (CoQ10) in ALS. CoQ10, a cofactor in mitochondrial electron transfer, may improve the mitochondrial dysfunction in ALS. In this study, CoQ10 was safe and well tolerated in 31 subjects treated with doses as high as 3,000 mg/day for 8 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 8 publications
1
83
0
Order By: Relevance
“…Treatment for conditions such as hypercholesterolemia, congestive heart failure, mitochondrial disorders, statin-induced CoQ depletion, and for enhancing exercise tolerance have used dosage similar to the low dose supplemented in the current study (Beal 1999;Rosenfeldt et al 2003Rosenfeldt et al , 2007Marcoff and Thompson 2007 ), whereas the high-CoQ dose can be related to doses used in clinical trials for the treatment of Parkinson's disease (Shults and Haas 2005) or Alzheimer's disease (trial NCT00117403), and doses up to 3,000 mg/day have been examined for short periods and determined to be void of toxic effects (Ferrante et al 2005). The highCoQ dose used in our study was beneficial for spatial learning and memory when used for a short period of time; when used lifelong, a similar dose led to significant deleterious effects (Sumien et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for conditions such as hypercholesterolemia, congestive heart failure, mitochondrial disorders, statin-induced CoQ depletion, and for enhancing exercise tolerance have used dosage similar to the low dose supplemented in the current study (Beal 1999;Rosenfeldt et al 2003Rosenfeldt et al , 2007Marcoff and Thompson 2007 ), whereas the high-CoQ dose can be related to doses used in clinical trials for the treatment of Parkinson's disease (Shults and Haas 2005) or Alzheimer's disease (trial NCT00117403), and doses up to 3,000 mg/day have been examined for short periods and determined to be void of toxic effects (Ferrante et al 2005). The highCoQ dose used in our study was beneficial for spatial learning and memory when used for a short period of time; when used lifelong, a similar dose led to significant deleterious effects (Sumien et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme Q10, a cofactor in the electron transfer chain, is also a scavenger of free radicals in lipid and mitochondrial membranes, and is thought to improve energy production by the mitochondrial membrane and the cell. Although the administration of high doses (up to 3,000 mg) of CoQ10 plus vitamin E (1,500 mg) to ALS patients was found to be generally safe, no clinical benefit was detected (41). Edaravone, a potent scavenger of free radicals that is approved in Japan for the treatment of ALS, was tested in 20 Japanese patients in a small double-blind study (145).…”
Section: Therapeutic Approaches To Alsmentioning
confidence: 99%
“…Reported adverse gastrointestinal effects: nausea, upset stomach and vomiting, during clinical trials showed that, because no dose-response relationship was defined, the gastrointestinal effects are not related with the active ingredient [8,9]. 1,200 mgCoq10 taken daily produces no adverse side effects and levels as high as 3,000 mg/day were tested without adverse effects; although at this level there is no adequate product safety information [9][10][11]. Taken orally, Coq10 in a crystalline form is poorly absorbed.…”
Section: Pharmacokinetic Parameters Of Coq10mentioning
confidence: 99%